Excavating the fossil record of spiral galaxies - Peterken, Thomas (2020)
Despite spiral galaxies being extremely common in our local neighbourhood, their formation, growth, and dynamics are not fully understood. However, the spatial variation in the properties of stellar populations contained within spiral galaxies are expected to bear the imprint of some of the past and present physical processes driving global and local structure and dynamics. Combining modern integral-field spectroscopic galaxy surveys with spectral fitting methods offers an unprecedented opportunity to peer into the stellar population "fossil record" and how it varies between and within spiral galaxies. By obtaining a full star-formation history at every location, it is possible to construct images denoting the spatial distribution of stars of different ages across the galaxy. In this thesis we explore how such a "time slicing" technique can be applied to data from the SDSS-IV MaNGA survey, and show that this approach can provide insights into the formation and the internal structure of spiral galaxies.